Advanced kitchen automation and monitoring using IoT / Ahmad Faiz Hakim Ahmad Nazri - Ahmad Nazri, Ahmad Faiz Hakim (2024)
Automation system in general has becoming popular around the globe because of its features that makes life easier and minimizes extra work loads. There is a strong need for ongoing development and modernization of these systems given their substantial contribution to provide convenience, safety, and security in the kitchen. In this current digital era, smartphones have become a necessity for every individual and making use of its capabilities to control and monitor a system makes life easier and more manageable. Since a household kitchen holds significant importance in any home environment and ensuring safety is crucial during kitchen related activities. It was shown that a household kitchen is a place of various potential hazards such as gas leaks, fires, unbalanced temperature and humidity in the environment and a lack of security. As a result, thousands of households have become the victim of housefires and robbery because the safety was neglected by the individual. In terms of automation, the kitchen is often times disregarded and this creates an opportunity to further improve its system with the application of technology. This project aims to provide a dedicated system that automates and monitors the kitchen environment using internet of things (IoT) where electronic components are able to communicate, control, share real time data via smartphones and take actions based on their instructions by utilizing sensors and connectivity. Furthermore, this project also aims to design the graphical user interface (GUI) using Blynk console in order to provide smooth interactions with the automated kitchen system. With this, the embedded system will provide aid for the kitchen automation and monitoring as well as reducing the risk of exposing to any harmful hazards